Patient-reported Anxiety: A Possible Predictor of Pediatric Inflammatory Bowel Disease Health Care Use. Issue 9 (September 2016) - Reigada, Laura C.; Satpute, Ankita; Hoogendoorn, Claire J.; Cohen, Barry H.; Lai, Joanne; Bao, Ruijun; Dubinsky, Marla C.; Benkov, Keith J.
Abstract : Background: Anxiety is linked with adverse health-related outcomes and increased health-seeking behaviors among patients with chronic illness. Yet, this relationship has received little attention in pediatric inflammatory bowel disease. The aim of this study was to examine whether anxiety symptoms predicted youth at increased risk for repeated disease relapse and greater gastrointestinal health care use over the subsequent 12 months. Methods: Eighty-six pediatric patients aged 11 to 18 years (M = 14.7, SD = 2.0), and their caregivers completed a validated anxiety questionnaire during a gastrointestinal specialty appointment (baseline). Medical records were reviewed for the subsequent year to record the number of disease relapses and gastrointestinal health care services and generate disease activity scores at baseline and 12 months. Analysis of variance was used to examine anxiety levels between those who experienced ⩽1 versus ≥2 disease relapses. Poisson regressions were used to model the relationship between child- and caregiver-reported anxiety and health care use, controlling for disease activity. Results: The sample was predominantly white (81%) and male (56%). Patients with higher anxiety at baseline (M = 19.6; SD = 13.7) had more frequent (≥2) disease relapses compared with those with lower anxiety at baseline (M = 12.6; SD = 10.3). Higher anxiety, irrespective of reporter, also predicted greater total gastrointestinal health care use ( P < 0.01). This included hospital-based interventions ( P < 0.01), but not office encounters or outpatient endoscopic procedures. Findings remained significant after controlling for disease severity ( P < 0.05). Conclusions: Assessment of anxiety may be one mechanism by which to identify those youth who are most vulnerable for disease exacerbation and costly interventions in the near future. Abstract : Article first published online 2 August 2016.